Harry Potter and the Order of the Phoenix [videorecording (DVD)] - Yates, David, 1963-; Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Rowling, J. K. (Warner Bros. Entertainment, 2016)
As Harry enters his fifth year at Hogwarts Academy, rumors of Lord Voldemort's return divide the wizarding world, and despite the insistence that there is no danger Harry and his friends start a group called Dumbledore's Army to prepare for a battle withLord Voldemort and his followers.